THE MODELLING OF TRAFFIC ON THE RAILWAY IN THE PROGRAM OPENTRACK (Perner's Contacts, 2009)
The paper is focused on modelling of traffic on the railway lines and the necessary software for it. Article also summarizes the findings of the project operate on the rationalization of traffic and transport infrastructure on non-corridor lines, which has been solved by Department of Transport Technology and Control.